(untitled) (Research, Society and Development, 2021)
The present study aims to demonstrate the results of the impact of bariatric surgery on non-alcoholic fatty liver disease through secondary sources available in the literature. A literature review was carried out with the descriptors "Non-alcoholic Fatty Liver Disease" OR "NAFLD" AND "Bariatric Surgery"; “Doença Hepática Gordurosa não Alcoólica” OR “DHGNA” AND “Cirurgia Bariátrica” in the databases: Latin American and Caribbean Health Sciences Literature, through the Virtual Health Library, and Medical Literature Analysis and Retrieval System Online (Medline), through PubMed. Cohort-type studies addressing the effects of bariatric surgery on non-alcoholic fatty liver disease published in the last 5 years were included in the review. Thirty-one studies were identified, of which 10 were excluded for not performing postoperative evaluation and 8 were excluded for not containing the methodological criteria, totaling 13 studies. The current literature presents data suggestive of the association between bariatric surgery and the regression of non-alcoholic fatty liver disease, however, the studies observed present wide variations in methodological applications and samples with heterogeneous profiles, which makes it difficult to generalize the results. More studies are needed so that it is possible to document with greater evidence and reproducibility the action of different types of bariatric surgery on the rate of this liver disease regression.